System identification and controller design for individual pitch and trailing edge flap control on upscaled wind turbines. Issue 6 (7th August 2015) - Chen, Zhenrong J.; Stol, Karl A.; Mace, Brian R.
Abstract: Active load reduction strategies such as individual pitch control (IPC) and trailing edge flap (TEF) actuation present ways of reducing the fatigue loads on the blades of wind turbines. This may enable development of lighter blades, improving the performance, cost effectiveness and viability of future multi‐megawatt turbine designs. Previous investigations into the use of IPC and TEFs have been limited to turbines with ratings up to 5 MW and typically investigate the use of these load reduction strategies on a single turbine only. This paper extends the design, implementation and analysis of individual pitch and TEFs to a range of classically scaled turbines between 5 and 20 MW. In order to avoid designing controllers which favour a particular scale, identical scale‐invariant system identification and controller design processes are applied to each of the turbines studied. Gain‐scheduled optimal output feedback controllers are designed using identified models to target blade root load fluctuations at the first and second multiples of the rotational frequency using IPC and TEFs respectively. The use of IPC and TEFs is shown in simulations to provide significant reductions in fatigue loads at the blade root. Fatigue loads on non‐rotating components such as the yaw bearing and tower root (yaw moment) are also reduced with the use of TEFs. Individual pitch performance is seen to be slightly lower on larger turbines, potentially due to a combination of reduced actuator bandwidth and movement of the rotational frequency of larger turbines into a more energetic part of the turbulent spectrum. However, TEF performance is consistent irrespective of scale. Copyright © 2015 John Wiley & Sons, Ltd.